2011
DOI: 10.4048/jbc.2011.14.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Small Bowel Metastasis from Breast Cancer

Abstract: The common sites of metastasis of breast cancer are bone, lung, and liver, but gastrointestinal metastasis from breast cancer is rare. We experienced a case of solitary ileal metastasis from breast cancer. A 45-years-old woman presented with melena for several weeks. She showed no other abdominal symptoms. Colonoscopy findings showed an ulcerative mucosal lesion in the terminal ileum, and biopsy was performed. Pathologic examination revealed metastatic carcinoma, originated from breast. The tumor cells were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…He also found that LC was prone to metastasize in a more “diffuse” fashion, with multiple tiny nodules that became confluent, while DC metastases formed nodular masses. Our patient had a metastasis of DC to the small bowel, which is a rare event but has been described previously [ 6 , 8 11 ].…”
Section: Discussionmentioning
confidence: 55%
“…He also found that LC was prone to metastasize in a more “diffuse” fashion, with multiple tiny nodules that became confluent, while DC metastases formed nodular masses. Our patient had a metastasis of DC to the small bowel, which is a rare event but has been described previously [ 6 , 8 11 ].…”
Section: Discussionmentioning
confidence: 55%
“…Of those cases, the original breast cancer is usually lobular with receptor positive histology that effects the terminal ileum rather than the rest of the small bowel [4]. Our case is one of few instances where invasive lobular carcinoma metastasizes to the proximal small bowel [19] and the first case reported in the US of triple negative invasive lobular carcinoma metastasizing to the jejunum [20].…”
Section: Resultsmentioning
confidence: 84%
“…Primary cancers of the colon, ovary, uterus, and stomach are usually spread to the small bowel by direct invasion or intraperitoneal spread, whereas primary cancers from the breast, lung, and melanoma metastasize to the small bowel by a hematogenous route. 8 The overall incidence of metastatic small bowel cancer is very low, and as mentioned earlier, most metastatic cancers have neither specific symptoms nor signs until they cause small bowel obstruction. Therefore, it is very difficult to detect metastatic small bowel cancer.…”
Section: Discussionmentioning
confidence: 97%